Literature Review: Early Childhood Parenting Efforts in Dual Earner Family - Anjani, Ratna; Mashudi , Esya Anesty; Nuroniah, Pepi (Aulad: Journal on Early Childhood, 2024)
The phenomenon of dual earner families, where both parents work outside the home, is increasingly prevalent in modern Indonesian society. This study aimed to examine early childhood care efforts in dual earner families in Indonesia. This research uses a literature review method with a scoping review technique to select relevant literature. Literature sources were searched online through the Google Scholar database through the Publish or Perish (POP) application, SpringerLink and ScienceDirect websites, and google searches. The results showed that dual earner families face significant challenges in balancing the demands of work with childcare. Although this model provides economic benefits, time constraints often lead to dependence on external caregivers, which can have an impact on child development, especially in parent-child interactions. Key challenges include sociological, psychological, economic and policy aspects. To address this, a comprehensive strategy involving supportive policies, the role of communities, the utilization of technology, as well as government intervention in providing supportive infrastructure is required. This research is expected to be an initial stepping stone for further empirical studies that are more in-depth about early childhood care in dual earner families in Indonesia